Occupational psychosocial risk factors: methods and assessment tools - Víctor H. Charria O; Kewy V. Sarsosa P; Felipe Arenas O (Universidad de Antioquia, 2011)
Objective: This review's aim is to analyze the basic conditions required for the assessment of occupational psychosocial risk factors within organizational contexts. Methodology: the review incorporates the main concepts that have been used to identify the causes of occupational stress, emphasizing the Demand - Control and the Effort - Reward - Imbalance models. Results: the authors show some methodologies and instruments that have exhibited high reliability for identifying psychosocial factors in different organizational contexts in different countries. Likewise, they highlight the case of Colombia; a country which, despite having few validated instruments, shows significant advance in this regard after the birth of resolution 2646 of 2008 and the construction of the battery of instruments for the assessment of Psychosocial Risk Factors by the Ministry of the Social Protection in 2010.